MANAGING PLANT INVASIONS USING LEGISLATION TOOLS: AN ANALYSIS OF THE NATIONAL AND REGIONAL REGULATIONS FOR NON-NATIVE PLANTS IN ITALY - Brundu, G.; Armeli Minicante, S.; Barni, E.; Bolpagni, R.; Caddeo, A.; Celesti-Grapow, L.; Cogoni, A.; Galasso, G.; Iiriti, G.; Lazzaro, L.; Loi, M. Cecilia; Lozano, V.; et al. (Annali di Botanica, 2020)
The integration of international, national and local regulations is one of the fundamental steps for preventing, controlling and managing biological invasions. The aim of the present study is to present and analyse, for the first time, the list of all non-native plant species that are regulated in Italy by the European, Italian and regional legislation in force. To date, there are 147 non-native plant taxa regulated. This number includes the 36 invasive alien plants of European Union concern and additional 111 taxa (95 species and 16 collective taxa) that have been listed at the regional level alone. A total of 19 plants of European Union concern and 95 regulated plants are present in the wild in at least one administrative region. The majority of the 95 species that are listed at the regional level alone are woody species (23 trees, 9 shrubs, 6 woody vines), followed by 29 herbs (19 annual herbs, 10 perennial herbs) and 11 aquatic plants. By presenting the regulated species and by identifying the most relevant species, the present study will provide an important tool to support plant invasion research and management and for the application of Regulation (EU) no. 1143/2014 on invasive alien species.